Role of cholinergic and adrenergic pathways of the medial septal area in the control of water intake and renal excretion in rats - Leite, Darlene Ferreira [UNESP]; Camargo, Luiz Antonio de Arruda [UNESP]; Saad, Wilson Abrão [UNESP]; Renzi, Antonio [UNESP]; Fóglia, Silvia [UNESP]; Luca Junior, Laurival Antonio de [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 1992)
In this study, we investigated an interaction between noradrenergic and cholinergic pathways of the medial septal area (MSA) on the control of water intake and urinary electrolyte excretion by means of injection of their respective agonists. Noradrenaline (a nonspecific α-adrenergic agonist) and clonidine (an α2-adrenergic agonist), but not phenylephrine (an α1-adrenergic agonist), induced natriuresis and kaliuresis. α-Adrenergic activation had no effect on the natriuresis and kaliuresis induced by carbachol (a cholinergic agonist) and it inhibited the antinatriuresis and antikaliuresis induced by isoproterenol (a ß-adrenergic agonist). Interactions related to volume excretion are complex. α-Adrenergic activation induced a mild diuresis and inhibited the antidiuresis induced by isoproterenol, but phenylephrine combined with carbachol induced antidiuresis. The water intake induced by carbachol was inhibited by clonidine and noradrenaline, but not phenylephrine. These results show an asymmetry in the interaction between α-adrenergic and cholinergic receptors concerning water intake and electrolyte excretion. © 1992.
Keywords: Adrenergic receptors; Cholinergic receptors; Diuresis; Kaliuresis; Natriuresis; Thirst; Water intake; Alpha adrenergic receptor; Beta adrenergic receptor; Carbachol; Cholinergic receptor stimulating agent; Clonidine; Isoprenaline; Noradrenalin; Phenylephrine; Animal experiment; Animal tissue; Controlled study; Diuresis; Fluid intake; Histology; Intracerebral drug administration; Kaliuresis; Male; Natriuresis; Nonhuman; Priority journal; Rat; Septum nucleus; Urinary excretion; Animal; Carbachol; Clonidine; Drinking; Isoproterenol; Kidney; Male; Mesencephalon; Neural Pathways; Norepinephrine; Parasympathetic Nervous System; Phenylephrine; Potassium; Rats; Sodium; Support, Non-U.S. Gov't; Sympathetic Nervous System; Urodynamics; Animalia